MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MELALUI PROBLEM BASED LEARNING DENGAN PEER FEEDBACK ACTIVITY - Endang Retno Winarti; Budi Waluya; Rochmad Rochmad (Jurnal Pembelajaran Matematika, 2018)
Abstract: The study aims to improve students' critical thinking skill in solving problems and examine their attitudes in learning through problem-based learning with peer feedback activities in an online discussion forum. This study uses a group post-test pre-test design. Pre-test and post-test are employed to measure critical thinking skill based on cognitive levels from Bloom. In measuring students’ attitudes in learning, questionnaires are applied. The findings show that there is an increase in critical thinking skill and students’ attitudes towards the application of problem based learning model with peer feedback activities in an online discussion forum.Keywords:Critical Thinking, Peer Feedback Activity, Problem Based Learning.